Holocene environmental instability in the wetland north of the Tiber delta (Rome, Italy): sea-lake-man interactions - Di Rita, Federico; Celant, Alessandra; Magri, Donatella (JOURNAL OF PALEOLIMNOLOGY, 2010)
Combined analyses of pollen, seeds, woods, micro-charcoal and non-pollen palynomorphs from Stagno di Maccarese, an artificially dried out coastal basin north of the Tiber delta now occupied by the Fiumicino Airport (Rome, Italy), document marked vegetation and environmental changes during the last 8300 years. Between 8300 and 5400 cal. a BP dense mixed deciduous and evergreen forests surrounded a eutrophic freshwater basin. An abrupt change around 5400 cal. a BP marks the transition to a marshy environment, due to a lowering of the water table. An increase of cereals and micro-charcoals matches the presence of a nearby Eneolithic settlement. Between 5100 and 2900 cal. a BP there is a remarkable expansion of riparian trees, indicating an increase of the water level. Between 2900 and 2000 cal. a BP, a new development of marshlands points to a progressive lowering of the lake. After 2000 cal. a BP, during the Roman exploitation of the area, an expansion of arboreal vegetation is recorded, characterized by evergreen and deciduous oak-dominated forests, while an extensive chenopods marshland matches the presence of saltworks. On the whole, the Stagno di Maccarese area appears very unstable, due to changes in lake level, introgression of marine water, eutrophic phases, flood events, desiccations and openings of the forest vegetation.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Hydrological changes; Plant macrofossils; Pollen analysis; Saltworks; Tiber delta